2022
DOI: 10.1111/cdep.12464
|View full text |Cite
|
Sign up to set email alerts
|

Ecological validity in measuring parents’ executive function

Abstract: Parents' executive functions (EFs), or cognitive skills facilitating thought and behavior management, are meaningful correlates of parenting behavior. EFs are theorized to support parents in inhibiting reactive responses, managing information during parent-child interactions, and adapting to novel developmental demands.Less effective EFs associate with risk for harsh parenting and physical abuse, underscoring the importance of research on parental EFs in promoting healthy child development. Yet, despite the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Moreover, there is extensive evidence that parental executive function is related to other parenting behaviors (see Bridgett et al, 2017; Deater-Deckard et al, 2010; Sturge-Apple et al, 2020, for a few select examples), and the four studies identified in this review that examined effortful control and ERSBs (Cumberland-Li et al, 2003; Davenport et al, 2011; Valiente et al, 2007; Zeytinoglu et al, 2017) all identified significant associations. Further understanding the extent to which parental executive function and effortful control—assessed in ecologically valid ways (Diercks et al, 2022)—predict ERSBs will further the field’s theoretical understanding of emotion socialization.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is extensive evidence that parental executive function is related to other parenting behaviors (see Bridgett et al, 2017; Deater-Deckard et al, 2010; Sturge-Apple et al, 2020, for a few select examples), and the four studies identified in this review that examined effortful control and ERSBs (Cumberland-Li et al, 2003; Davenport et al, 2011; Valiente et al, 2007; Zeytinoglu et al, 2017) all identified significant associations. Further understanding the extent to which parental executive function and effortful control—assessed in ecologically valid ways (Diercks et al, 2022)—predict ERSBs will further the field’s theoretical understanding of emotion socialization.…”
Section: Discussionmentioning
confidence: 99%
“…In advancing this line of research, there are a variety of tools researchers could use to assess EF. Diercks et al (2022) briefly outlined current measures of EF. However, they also encouraged researchers to develop new measures that more closely represent the types of EF skills required in parenting.…”
Section: Discussionmentioning
confidence: 99%
“…We relied on EF tasks that were decontextualized and primarily tapped affectively and motivationally neutral (i.e., "cool") EF processes. It is possible that affectively salient ("hot") tasks may be differentially related to parenting behaviors and future studies should incorporate both tasks into process models (Diercks et al, 2022). Additionally, working memory, inhibition, and cognitive flexibility were each measured with single respective tasks.…”
Section: Limitationsmentioning
confidence: 99%
“…Scientific inquiry into parental EF is a relatively recent development (Crandall et al, 2015) but emerging evidence from various fields suggests that EFs are critical to the development and maintenance of optimal parenting behavior (Crandall et al, 2015; Deater-Deckard & Sturge-Apple, 2017; Diercks et al, 2022). This is because parental self-regulation is supported by a suite of executive processes (i.e., working memory capacity, inhibitory control, and flexible task shifting) that serve to modulate and control reflexive reactions and efficiently integrate and process environmental stimuli in service of reflective, contextually sensitive parenting.…”
Section: Parental Ef As a Spillover Mechanismmentioning
confidence: 99%